Ontmoetingen 1930-1942 - Rens, Jef (Antwerpen: De Nederlandsche Boekhandel; Amsterdam, 1984)
"Jef Rens Ontmoetingen met o.m. Marcel Déat, Gust Demuynck, Herman Vos, Corneel Mertens, Joseph Bondas, Emile Vandervelde, Isabelle Blume, Achille van Acker, Hendrik de Man"